2016
DOI: 10.1108/afr-02-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farm financial performance: firm, year, and size effects

Abstract: Purpose The purpose of this paper is to evaluate dairy farm financial performance over time utilizing farm financial ratios from three university business analysis programs. The evaluation includes measures of profitability, solvency, and liquidity by herd size. Design/methodology/approach Financial ratios to reflect profitability (rate of return on assets), solvency (debt to asset ratio), and liquidity (current ratio) were collected from Cornell University, Michigan State University, and the University of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 7 publications
0
21
0
4
Order By: Relevance
“…To better capture the sample's heterogeneity, we group local and regional food marketers into high- and low-performing quartiles by profitability and conduct statistical tests across quartiles. There are many measures of profitability, but in this case we chose to use a farm's reported ROA, a commonly used metric to evaluate the profitability of farm businesses, to sort farms into quartiles as a way to disentangle what differences may exist among the most and least profitable farms (e.g., Ho et al 2013, Wolf et al 2016). The use of a “standardized” measure like ROA, may allow some expected and interesting cases (such as lean farms with few owned assets that are aggressively pursuing high-end produce and product markets) to emerge more clearly.…”
Section: Methodsmentioning
confidence: 99%
“…To better capture the sample's heterogeneity, we group local and regional food marketers into high- and low-performing quartiles by profitability and conduct statistical tests across quartiles. There are many measures of profitability, but in this case we chose to use a farm's reported ROA, a commonly used metric to evaluate the profitability of farm businesses, to sort farms into quartiles as a way to disentangle what differences may exist among the most and least profitable farms (e.g., Ho et al 2013, Wolf et al 2016). The use of a “standardized” measure like ROA, may allow some expected and interesting cases (such as lean farms with few owned assets that are aggressively pursuing high-end produce and product markets) to emerge more clearly.…”
Section: Methodsmentioning
confidence: 99%
“…It measures how efficiently a firm can create profit using their invested assets in a given year, accounting for the opportunity cost of money. Although not commonly used in profit frontier estimation, the use of a ‘standardized’ measure like ROA may allow some expected and interesting cases (such as lean management farms with few owned assets that compete through aggressively pursuing high end produce and product markets) to emerge more clearly (e.g., Ho et al , 2013; Wolf et al , 2016). In contrast, gross measures, such as operating profit, may mask some interesting aspects of farms participating in direct markets.…”
Section: Empirical Approachmentioning
confidence: 99%
“…From the standpoint of the USDA and private foundations that provide funding in this area, understanding the factors that influence efficiency will enable them to better target their resources and support local and regional food system development. As one example, the Farm Service Agency is striving to provide more capital to farms participating in these markets, but needs to understand the underlying factors that allow farms to be viable (and repay their loans) (USDA FSA, 2016). Additionally, in 2015, the USDA Risk Management Agency began piloting Whole-Farm Revenue Protection, a program that provides an insurance plan for diversified producers selling through local and regional food markets (USDA RMA, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vasiliev et al [22] identified the same patterns for Estonian farms. According to Wolf et al [23], this relationship varied significantly throughout different stages of the economic cycle. However, Bojnec and Latruffe [24], after analysing the links between farm size, agricultural subsidies, and farm performance in Slovenia, observed a different pattern for Slovenian farms as small farms were more profitable than large farms.…”
Section: Introductionmentioning
confidence: 99%